Unlocking the Potential of Blockchain for Secure and Efficient Global Supply Chains - Sari, Intan Tenisia Prawita; Rauf, Mohamad Iqbal Abdul; Zulfikri, Agung (Sinergi International Journal of Logistics, 2024)
Blockchain technology is rapidly transforming global supply chain management by introducing new levels of transparency, traceability, and operational efficiency. This narrative review aims to evaluate the impact of blockchain integration on supply chain transparency across various sectors. Using a literature-based approach, studies were retrieved from leading databases such as Scopus, Google Scholar, and Web of Science, focusing on applications in food, pharmaceuticals, logistics, and sustainability. The results indicate that blockchain enhances traceability and transparency through decentralized ledgers, enabling real-time data access and reducing fraud, errors, and inefficiencies. Case studies show significant improvements in product tracking, cost reduction, and consumer trust, particularly when combined with technologies like IoT and smart contracts. However, challenges persist, including high implementation costs, limited technical skills, and unequal adoption between large firms and SMEs. Systemic issues such as regulatory uncertainty and lack of stakeholder collaboration further hinder implementation. The discussion highlights the role of public policy and data governance in facilitating adoption and calls for collaborative ecosystems that support blockchain deployment. Limitations in geographic scope, methodological design, and long-term impact assessment were identified, suggesting avenues for future research. Ultimately, blockchain holds significant promise for building sustainable, secure, and efficient supply chains, provided that structural barriers are addressed through targeted policy and inclusive innovation strategies.